0137 Acute cognitive effects of MRI related magnetic fields: the role of vestibular sensitivity. (23rd June 2014) - van Nierop, Lotte; Slottje, Pauline; van Zandvoort, Matine; Kingma, Herman; Kromhout, Hans
Abstract : Objectives: Movement in the magnetic fields around MRI systems showed acute negative effects on concentration, memory, visuo-spatial orientation and postural body sway. A crucial role of the vestibular system has been hypothesised. We aimed to gain more insight whether subjects with a relatively (un)sensitive vestibular system performed differently on cognitive tasks when (moving) in a the static magnetic field of an MRI scanner. Method: In a double blind randomised cross over experiment 36 healthy volunteers underwent several cognitive tasks in 4 experimental sessions. Two were exposure conditions near a 7 Tesla (T) MRI system with personal exposure of 1.0 T. In one of these conditions additional time-varying magnetic fields of 2.4 T/s were induced by making standardised head movements. Of the two sham conditions (0 T) one was with and the other without such head movements. Vestibular sensitivity of each subject was assessed by the rotary chair test, the caloric reflex test and self-reported sensitivity to motion sickness. Results: Linear mixed models are currently in progress to test cognitive performance in a magnetic field for subjects with a low, normal and high sensitive vestibular organ. Preliminary results seem to suggest some differential cognitive effects of magnetic field exposure according to relative vestibular sensitivity. Further results will be presented at the conference. Conclusions: These findings are important to better understand a possible working mechanism evoking these cognitive effects. Moreover, these finding can form a basis for the design of relevant protective and precautionary control measures for employees working close to an MRI system.